Hospitality Program Selection Criteria: A Comparison of International Undergraduate, Master's, and Doctoral Students. Issue 3 (3rd July 2019) - Choi, Eun-Kyong (Cindy); Ruetzler, Tanya Maren; Wang, Anqi
ABSTRACT: Because of their cultural and financial contributions to their host institutions and communities, higher education has recruited more international students to its institutions. In order to understand why international students in hospitality and tourism management programs choose one school over other options, the present study identified eight factors influencing international students' hospitality and tourism management program selection in the United States. Results from a multivariate analysis of variance followed by univariate analyses of variance showed differences in the importance of five out of eight factors among undergraduate, master's, and doctoral international students. Detailed discussions and implications are presented.